Onshore Wind Energy Potential in Sri Lanka - Cai, B.; Sritharan, S. (University of Jaffna, 2022)
Wind power production has grown substantially in the world over the past two decades, making wind the fastest-growing non fossil energy source. The growing rate of installed capacity of wind power was reported to be less than 20% from 2000 to 2019 and anticipated to increase by another 50% by the end of 2023. Wind resources in Sri Lanka show varied wind energy potential in different regions. Adapting new wind technologies, such as large turbines and tall towers, can optimize wind generation in different regions while increasing the wind power potential for the country. In this study, the wind tower hub height is used as the primary factor to evaluate the impact of new technologies. It is shown that by increasing the tower height by 20-40 m over the standard 80 m hub height, wind power can be generated at a competitive cost in Sri Lanka.
Keywords: Wind energy; Tall wind tower; Annual energy production; Capacity factor; Levelized Cost of Energy; Sri Lanka